Finite Element Analysis of Stress on Cross-Wavy Primary Surface Recuperator Based on Thermal-Structural Coupling Model - Xiaohong Gui; Xiange Song; Haiwen Gong; Dianbao Yao; Ruogu Chen; Guang Xu (Advances in Materials Science and Engineering)
In order to study the stress, strain and deformation of the recuperator, the thermal-structural coupling finite element analysis model of cross-wavy primary surface recuperator of gas microturbine was established. The stress of cross-wavy primary surface recuperator after operation under design conditions was analyzed by finite element method. The reliability of the material selected for the recuperator was verified, and the effects of pressure ratio and gas inlet temperature on stress and displacement of the recuperator were analyzed. The research results show that the maximum stress and strain on the gas outlet side of the recuperator are higher than the maximum stress and strain on the gas inlet side when only pressure is considered, and the result is the opposite when pressure and thermal stress are considered. The air passage of the recuperator deforms to the side of the gas passage, the air passage becomes larger, and the gas passage shrinks. With the increase of pressure ratio between air side and gas side, the maximum stress of recuperator passage also increases. When the pressure ratio increases to 8.4, the strength limit of the heat exchange fin material is reached. When the gas and air outlet temperatures remain unchanged and the thermal ratio decreases, as the gas inlet temperature increases, the maximum stress increases. For every 50 K increase in the gas inlet temperature, the maximum stress of the recuperator increases by about 2.3 MPa. The research results can be used to guide the designing and optimization of recuperator.